Biomechanical Study of Posterior Lumbar Interbody Fusion: A Review - Azmi, Muhammad Huzaifah; Mazlan, Muhammad Hazli; Md Salleh, NurSaliha; Hiromitsu Takano, Hiromitsu Takano; Jalli, Muhammad Hilmi; Razali, Muhammad Anas; Abdullah, Abdul Halim (IJATAE, 2023)
Degenerative disc disease is a spinal disorder in which the vertebral disc helps protect nerves and increase spine flexibility that begins to deteriorate. The syndromehappens in the lumbar spine, which is crucial in supporting the weight of the human body. The lumbar vertebrae are naturally larger to absorb the stress of carrying heavy objects. Many surgical treatments are available for this disorder, and the most common treatment is Posterior Lumbar Interbody Fusion (PLIF) surgery. However, a lot ofquestionable clinical effects related to this procedure, such as cage sinking into vertebral endplates, cage failure and cage relocation. This paper reviews the technical aspects of developing PLIF implants based on clinical, in-vitro, animal, prospective, and retrospective studies.The finite element analysis (FEA) approach has shown the most promising technique by offering virtual biomechanical assessments, low risk of implant failure and bone fractures, and satisfying patient-specific requirements. Many types of FEA software are available in the market, such as Ansys, ABACUS, and Mechanical Finder software. The ability of the software to develop heterogeneous bone models will give an extra advantage in improving the FEA accuracy in terms of stress and distributions and fracture risk assessment. The research approach, biomechanical assessment and data interpretation related to the development of the previous and existing studies will give an insightinto the research strategies and their restrictions. The FEA investigation can be utilized to optimize the mechanical characteristics of PLIF with various infill pattern designs and densities. Moreover, the further research analysis is still needed to improve interbody cage development.